1982
DOI: 10.1080/03015521.1982.10427884
|View full text |Cite
|
Sign up to set email alerts
|

‘Grasslands Roa’ tall fescue: Seedling growth and establishment

Abstract: Germination rate, root, and shoot growth of 'Grasslands Roa' S170, and a wild type tall fescue (Festuca arundinacea Schreb.) were compared with perennial ryegrass (Lolium perenne L.) in the glasshouse and field. There was little variation between tall fescues but S170 established slightly better than the others. Under moisture stress, the wild type was superior to the other tall fescues in germination and establishment. Ryegrass was markedly superior to all tall fescues because of much higher germination, root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
2
6
0
2
Order By: Relevance
“…Early seedling growth (Fig. 5) for the five cultivars in descending order was Maru, Nui, Roa, Wana, and Basyn which agrees with current information on their relative establishment rates (Lancashire et al 1980;Anderson 1982;Brock et al 1982;Lancashire & Brock 1983;Chapman et al 1985;Hume & Fraser 1985). Wana and Basyn, though emerging slowly and having only moderate responses to N in the first year, were the most productive cultivars in the second year.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Early seedling growth (Fig. 5) for the five cultivars in descending order was Maru, Nui, Roa, Wana, and Basyn which agrees with current information on their relative establishment rates (Lancashire et al 1980;Anderson 1982;Brock et al 1982;Lancashire & Brock 1983;Chapman et al 1985;Hume & Fraser 1985). Wana and Basyn, though emerging slowly and having only moderate responses to N in the first year, were the most productive cultivars in the second year.…”
Section: Discussionsupporting
confidence: 75%
“…Nui and Roa, though slightly depleted in seedling numbers by high rates of N at sowing, still had the most uniform swards in the second and third years with Roa showing little effect of its slower establishment. Brock et al (1982) suggested that Roa, because of its slower root growth, could be at a competitive disadvantage under low soil N but its competitive ability against the hawkweed in the field experiment was similar to Nui's over a wide range of N. However, small changes in competitive ability could have large effects on composition in mixed swards containing other species (Lancashire & Brock 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Roa tall fescue has always been slow to establish (Brock et al 1982), a problem common to many cultivars of tall fescue when compared with quick-establishing ryegrass. Two new tall fescue cultivars have recently been bred by AgResearch Grasslands-cv.…”
Section: A93064mentioning
confidence: 99%
“…En raigrás anual, que posee menor tamaño de semillas en comparación con otras gramíneas, su mayor establecimiento comparativamente con gramíneas perennes, tales como festuca, se pudo deber a la mayor tasa de crecimiento relativa (Garnier, 1992) que resulta en plantas más desarrollas que compiten mejor por recursos limitantes en un período de tiempo dado. Además ésta especie, presenta mayor tasa de movilización de reservas de almidón del endosperma hacia el embrión, que especies perennes como la festuca (Brock et al, 1982), posibilitando el logro de un mayor vigor de plántulas.…”
Section: Efecto De La Especie Y Cultivo Antecesorunclassified
“…Una característica importante de las semillas es su capacidad de movilizar reservas de carbohidratos desde el endosperma hacia los puntos de crecimiento, existiendo diferencias entre especies en la rapidez de movilización de reservas (Askin, 1994) que determinan diferencias en la velocidad de germinación; el raigrás anual es un claro ejemplo de esto, presenta mayor tasa de desdoblamiento del endosperma, comparativamente a otras gramíneas (Brock et al, 1982).…”
Section: Introductionunclassified